Weighted singular decomposition and weighted pseudoinversion of matrices - Galba, E. F. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For a rectangular real matrix, we obtain a decomposition in weighted singular numbers. On this basis, we obtain a representation of a weighted pseudoinverse matrix in terms of weighted orthogonal matrices and weighted singular numbers.